Strategi Kepemimpinan Transformasional dalam Optimalisasi Kurikulum Pendidikan Agama Islam Pondok Pesantren: indonesia - Kholadatur Rosyida; Agus Sulton Imami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Transformational leadership has become a crucial element in redefining the quality and direction of Islamic Education in the Islamic boarding school-based learning system. This research aims to explore how transformational leadership strategies contribute to the optimization of the Islamic Education curriculum through a visionary, charismatic, and value-oriented approach. Using a qualitative case study design, data was collected through interviews, observations, and documentation involving pesantren leaders, teachers, and curriculum managers. The research findings reveal three key patterns: the integration of inspirational leadership in curriculum innovation, the embodiment of visionary strategies in pedagogical practice, and the institutionalization of charismatic influence in educational transformation. These dynamics collectively reinforce moral values, teacher professionalism, and collaborative curriculum development. The novelty of this research lies in the identification of a spiritual leadership framework that combines managerial effectiveness with ethical integrity. This research shows that transformational leadership is crucial to implementing and sustaining value-based holistic curriculum reforms in Islamic educational institutions.